Online Learning Quality of Engineering Faculty Universitas Negeri Surabaya Towards Legal Entity State University - Edy Sulistiyo; Yuli Sutoto Nugroho; Lilik Anifah; Unit Three Kartini; Maulana Rizki Aditama; Rifqi Firmansyah; Sari Cahyaningtias (IJORER : International Journal of Recent Educational Research, 2022)
Analysis of the quality of the learning process is very important in teaching and learning activities in ensuring and maintaining the quality of learning well. In the teaching and learning process, the quality assurance instrument or learning quality is an instrument or tool that aims to improve quality in the education sector through observations and assessments produced by research on students. The objective of this research is to test the quality of the online learning process during the Covid-19 pandemic at the Faculty of Engineering (FT) of the State University of Surabaya (Unesa) towards a Legal Entity Higher Education (PTN-BH). The method used in this research is descriptive qualitative which aims to find out social phenomena from the point of view of students and lecturers. The result of this study is that from the ten statements given to respondents, all shown positive results. it can be concluded that Faculty of Engineering students and lecturers support Unesa to become a Legal Entity State University.